Lead-free relaxation ceramic material with tungsten bronze structure as well as preparation method and application of lead-free relaxation ceramic material

Through the design and preparation process of lead-free relaxation ceramic materials with tungsten bronze structure, the problems of low energy storage density and poor stability of lead-free dielectric ceramic materials are solved, and the performance of high energy storage density and high efficiency of ceramic capacitors is achieved. High power pulse system.

CN119285354APending Publication Date: 2025-01-10HANGZHOU INST FOR ADVANCED STUDY UCAS +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411358620.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-27
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

The existing lead-free dielectric ceramic materials have low energy storage density and poor stability, making it difficult to achieve miniaturization and integration of devices. The system has a small phase change lag and moderate dielectric constant, making it difficult to meet the needs of high energy storage density and lightweight.

Method used

Design a tungsten bronze structure lead-free relaxation ceramic material K2 (LaxGd1-x)Nb5O15-0.5mol%MnCO3 through specific chemical composition and preparation processes, including multiple mixing, drying, sieving, calcining, bonding and sintering Steps to optimize the microstructure and performance of ceramic materials.

Benefits of technology

It achieves high pressure withstand strength, low residual polarization strength, high saturation polarization strength, high energy storage density and energy storage efficiency. It is suitable for ceramic capacitors and dielectric capacitors in high-power pulse systems to meet the needs of lightweight.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119285354A_ABST
    Figure CN119285354A_ABST
Patent Text Reader

Abstract

The invention relates to a lead-free relaxation ceramic material with a tungsten bronze structure and a preparation method and application thereof, the chemical composition of a K2RENb5O15-based lead-free relaxation ceramic material is K2 (LaxGd1-x) Nb5O15-2.5 mol% MnCO3, and x is more than or equal to 0.25 and less than or equal to 1. The technical scheme is simple in composition and preparation process, has the characteristics of high breakdown strength, high energy storage density and the like, and is suitable for preparation and application of a ceramic capacitor and a dielectric capacitor in a high-power pulse system.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of functional ceramic materials, and in particular relates to a tungsten bronze structure lead-free relaxor ceramic material and a preparation method and application thereof. Background Art

[0002] With the rapid development of the electronic information industry, energy storage devices have increasingly become a hot research target. Ceramic dielectric materials have attracted widespread attention due to their high power density and fast charge and discharge rates. At present, it has become an inevitable trend for lead-free materials to replace lead-based materials, but lead-free dielectric ceramics have low energy storage density and poor stability, making it difficult to meet the requirements of device miniaturization and integration. Based on this technical defect, it is very necessary to develop a ceramic material that has a small phase change hysteresis, a moderate dielectric constant, a low overall structural density, and the function of achieving ultra-high energy storage density and lightweight. Summary of the invention

[0003] In view of the above technical problems, the purpose of the present invention is to provide a tungsten bronze structure lead-free relaxor ceramic material and a preparation method and application. This is specifically achieved through the following technical solutions:

[0004] A tungsten bronze structure lead-free relaxor ceramic material, the chemical composition of the ceramic material is: K2(LaxGd1-x)Nb5O 15 -0.5 mol% MnCO3, wherein x is a molar percentage, and 0≤x≤1, preferably 0.25≤x≤1.

[0005] A method for preparing a lead-free relaxor ceramic material with a tungsten bronze structure, comprising the following steps:

[0006] 1) According to K2RENb5O 15 Based on the chemical composition ratio of the lead-free relaxor ceramic material, the K source, Nb source, La source and Gd source are mixed for the first time, dried for the first time, sieved for the first time, and calcined to obtain the preliminary solid solution powder;

[0007] 2) Add K2RENb5O to the solid solution powder 15 A Mn source is added to the chemical composition of the base lead-free relaxor ceramic material in a stoichiometric ratio, and the ceramic final solid solution powder is obtained through a second mixing, a second drying, and a second screening.

[0008] 3) adding a binder to the final solid solution powder, mixing and granulating, and obtaining a ceramic green body through aging, molding and plastic removal;

[0009] 4) Sinter the ceramic blank to obtain K2RENb5O 15 Based on lead-free relaxor ceramic materials.

[0010] Furthermore, in step 1) and step 2), the K source is K2CO3, the Gd source is Gd2O3, the La source is La2O3, the Nb source is Nb2O5, and the Mn source is MnCO3.

[0011] Furthermore, the first mixing method is ball milling, the mass ratio of raw materials: grinding balls: alcohol is controlled to be 1:4-8:0.8-1.3, the grinding balls are any one of zirconia balls, zirconia columns, and agate balls, and the ball milling time is 4 hours; the mesh size of the first sieving is 20-80 meshes.

[0012] Furthermore, the calcination temperature is 1200-1300°C; the calcination time is 2-3h; and the heating rate is not higher than 2°C / min.

[0013] Furthermore, the second mixing method is ball milling, the mass ratio of raw materials: grinding balls: alcohol is controlled to be 1:4-8:0.6-1.2, the grinding balls are any one of zirconia balls, zirconia columns, and agate balls, and the ball milling time is 12 hours; the mesh size of the second sieving is 20 to 80 meshes.

[0014] Furthermore, the binder is at least one of polyvinyl alcohol, polyethylene glycol, polystyrene or methyl cellulose, the concentration of the binder is 6-8%, and the added amount is 6-8wt.% of the weight of the final ceramic solid solution powder.

[0015] Furthermore, the aging temperature is room temperature, the time is 18-26 hours, preferably 22-26 hours; the temperature of plastic discharge is 650-850°C, the insulation time is 1-24 hours, preferably 1-3 hours, and the heating rate of plastic discharge is not higher than 2°C / min.

[0016] Furthermore, in step 4), the sintering temperature is 1200-1300°C, the sintering time is 2-3 hours, and the heating rate is not higher than 2°C / min.

[0017] The above-prepared K2RENb5O 15 Application of lead-free relaxor ceramic materials in the preparation of ceramic components.

[0018] K2RENb5O prepared by the method of the present invention 15 The lead-free relaxor ceramic material has a simple composition and K2RENb5O prepared by component regulation and process optimization. 15 The lead-free relaxor ceramic has the characteristics of high compressive strength, low residual polarization strength and high saturation polarization strength, high energy storage density and energy storage efficiency, and has a low density. It is suitable for lightweight requirements such as ceramic capacitors and dielectric capacitors in high-power pulse systems. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1is the X-ray diffraction pattern of the ceramic material prepared in Examples 1-4 of the present invention;

[0020] Figure 2 The surface microscopic morphology of the ceramic material prepared in Examples 1-4 of the present invention;

[0021] Figure 3 1 is a comparison diagram of hysteresis loops of the ceramic components prepared in Examples 1-4 of the present invention. DETAILED DESCRIPTION

[0022] The present invention is further described below in conjunction with specific embodiments to facilitate a better understanding of the present technical solution.

[0023] The present invention provides a tungsten bronze structure lead-free relaxor ceramic material, K2RENb5O 15 The chemical composition of the lead-free relaxor ceramic material can be K2(LaxGd1-x)Nb5O 15 -2.5mol%MnCO3; wherein x is a molar percentage, 0≤x≤1, preferably 0.25≤x≤1.

[0024] The present invention has been verified through theoretical research and multiple experiments for K2RENb5O 15 Based on ceramic materials, by adjusting the ratio of different elements and introducing different ion radii, K2RENb5O 15 The base material exhibits excellent energy storage performance at room temperature. The ceramic material with the chemical composition provided by the present invention has high saturation polarization intensity, low residual polarization intensity, high energy storage density and energy storage efficiency, and is expected to be applied in the field of dielectric energy storage.

[0025] If the value of x is too large, the material will reach saturation polarization earlier, which is not conducive to improving the energy storage performance; if the value of x is too small, the material will exhibit a relaxor ferroelectric phase, which is also not conducive to energy storage.

[0026] The preparation method of the lead-free relaxor ceramic material of tungsten bronze structure comprises the following steps: firstly, a K source, a RE source and a Nb source are prepared according to the K2RENb5O 15 The chemical composition stoichiometric ratio of the KRN-based lead-free relaxor ceramic material is first mixed, first dried, and first screened, and then calcined and cooled to room temperature in the furnace to obtain a ceramic preliminary solid solution powder; then, a Mn source is added to the ceramic preliminary solid solution powder according to the chemical composition stoichiometric ratio of the KRN-based lead-free relaxor ceramic material, and a ceramic final solid solution powder is obtained after a second mixing, a second drying, and a second screening; then, a binder is added to the ceramic final solid solution powder and granulated, and a KRN-based lead-free relaxor ceramic blank is obtained after aging, molding, and plastic removal; finally, the K2RENb5O15-based lead-free relaxor ceramic material is obtained after sintering.

[0027] In some embodiments, the K source is K2CO3, the La source is La2O3, the Gd source is Gd2O3, the Nb source is Nb2O5, and the Mn source is MnCO3.

[0028] In some embodiments, the first mixing method can be ball milling, and the mass ratio of raw material: grinding ball: alcohol can be controlled to be 1:4-8:0.8-1.3. The grinding ball can be zirconia ball, zirconia column, agate ball, and the ball milling time can be 4 hours.

[0029] In some embodiments, the mesh size of the first screening may be 20-80 meshes.

[0030] In some embodiments, the calcination temperature may be 1200-1300° C.; the calcination time may be less than 2-3 hours; and the heating rate may be controlled to be 2° C. / min, so that the synthesis reaction of the KRN ceramics can fully occur.

[0031] In some embodiments, the powder can be briquetteed at 100-300 MPa after the first screening, and then the pressed block can be calcined for synthesis; at the same time, the block can be further crushed and sieved (for example, 20-80 mesh) after synthesis, thereby improving the efficiency of subsequent mixing processes such as ball milling and saving preparation time.

[0032] In some embodiments, the second mixing method can be ball milling, and the mass ratio of raw material: grinding ball: alcohol can be controlled to be 1:4-8:0.6-1.2. The grinding ball can be zirconia ball, zirconia column, agate ball, and the ball milling time can be 12 hours.

[0033] In some embodiments, the mesh size of the second screening may be 20-80 meshes.

[0034] In some embodiments, the binder may be at least one of polyvinyl alcohol, polyethylene glycol, polystyrene or methyl cellulose, the concentration of the binder may be 6-8%, and the amount added may be 6-8 wt.% of the weight of the final ceramic solid solution powder.

[0035] Aging can make the adhesive more evenly distributed in the powder, which helps the powder to be better formed. In some embodiments, the aging temperature can be room temperature (25°C) and the time can be 18 to 26 hours, preferably 22 to 26 hours.

[0036] In some embodiments, the molding may be performed by dry pressing, and the molding pressure may be 100 to 300 MPa.

[0037] In some embodiments, the temperature of the plastic discharge can be 600° C., and the holding time can be 2 hours; preferably, the heating rate of the plastic discharge is not higher than 2° C. / min.

[0038] In some embodiments, the sintering temperature may be 1200-1300° C.; the sintering time may be 2-3 hours; and the heating rate may be 2° C. / minute, so that the ceramic is easily formed without causing component segregation.

[0039] As an example, K2RENb5O 15 The lead-free relaxor ceramic material is processed into the required size, and after cleaning (such as ultrasonic cleaning), drying, silver coating, and silver firing, K2RENb5O can be obtained. 15 Based on relaxor ceramic components; wherein, the silver sintering conditions can be kept at 600-900°C for 10-30 minutes, and the heating rate can be controlled to be no higher than 2°C / minute.

[0040] Example 1

[0041] Tungsten bronze structure lead-free relaxor ceramic material (K2(LaxGd1-x)Nb5O 15 -2.5mol%MnCO3,x=0.75) comprises the following steps:

[0042] (1) According to the chemical composition ratio, potassium carbonate with a purity of 99%, niobium pentoxide with a purity of 99.93%, lanthanum trioxide with a purity of 99.99%, and gadolinium trioxide with a purity of 99.9% were weighed using an electronic balance (weighing accuracy to 0.001 g), the weighed raw materials were mixed and placed in a nylon can, anhydrous ethanol was added to the can, and the nylon can was placed on a planetary ball mill with zirconium oxide columns and zirconium oxide balls of different sizes as the medium for mixing for 4 hours. The zirconium oxide columns included two different diameters. 15mm×15mm high and 7.5mm×7.5mm high, the zirconia balls include one size: 10mm in diameter, and the mass ratios of the three zirconia columns and balls are 4:2:3. After ball milling, pour out and dry in a baking oven, and then sieve with a 40-mesh nylon sieve. The sieved mixed powder is pressed into a cylindrical block with a size of 65mm in diameter×20mm in height on a press, synthesized at 1180°C for 4 hours, and then smashed through a 40-mesh sieve to obtain a ceramic pre-solid solution powder;

[0043] (2) placing the obtained ceramic preliminary solid solution powder into a nylon can again, adding manganese carbonate powder with a powder molar ratio of 2.5%, adding anhydrous ethanol not higher than 2 / 3 of the height of the can into the can, placing the nylon can on a planetary ball mill with zirconia columns and zirconia balls of different sizes as the medium for mixing for 12 hours, then pouring it out and drying it in a baking oven, and then sieving it with a 40-mesh nylon sieve to obtain the ceramic final solid solution powder;

[0044] (3) adding a polyvinyl alcohol aqueous solution with a concentration of 7wt.% to the final ceramic solid solution powder (ground ceramic powder), wherein the amount of the polyvinyl alcohol aqueous solution added is 6% of the mass of the ceramic powder, and then uniformly granulating, passing through a 40-mesh sieve, aging, and compression molding to obtain a small cylinder with a size of 13mm in diameter and 1mm in height, and then performing plastic molding; sintering the obtained green body after plastic molding in an atmospheric atmosphere at a sintering temperature of 1250°C for a holding time of 2-3 hours, and naturally cooling to room temperature to obtain the KRN-based lead-free relaxor ceramic material;

[0045] The KRN-based lead-free relaxor ceramic material is processed, cleaned, dried and electroded to obtain a ceramic element.

[0046] Example 2

[0047] In this embodiment, K2RENb5O 15 The preparation method of the lead-free relaxor ceramic material based on KRN is as described in Example 1, except that the molecular formula of the lead-free relaxor ceramic material based on KRN is K2(LaxGd1-x)Nb5O 15 -2.5 mol% MnCO3, x=0.1.

[0048] Example 3

[0049] The preparation method of the ceramic material in this embodiment refers to that in Embodiment 1, the main difference is that the molecular formula of the ceramic material is K2(LaxGd1-x)Nb5O 15 -2.5 mol% MnCO3, x=0.5.

[0050] Example 4

[0051] The preparation method of the ceramic material in this embodiment refers to that in Embodiment 1, the main difference is that the molecular formula of the ceramic material is K2(LaxGd1-x)Nb5O 15 -2.5 mol% MnCO3, x=0.25.

[0052] The X-ray diffraction patterns of the ceramic materials obtained in Examples 1-4 of the present invention are shown in Figure 1 .from Figure 1 It can be seen that the KRN ceramics prepared by the preparation method provided by the present invention have no impurity phase.

[0053] The surface microscopic morphology of the ceramic materials prepared in Examples 1-4 of the present invention is shown in Figure 2 ,from Figure 2 It can be seen that the ceramic material prepared by the preparation method provided by the present invention is sintered densely.

[0054] The prepared ceramic element was subjected to a unipolar hysteresis loop test at room temperature and 10 Hz. The hysteresis loop comparison diagram of the ceramic element prepared in Examples 1-4 of the present invention is shown in FIG. Figure 3 As shown. Figure 3 It can be seen that the energy storage density of the ceramic element prepared in Example 1 increases with the increase of the electric field, and the maximum energy storage density is 4.46J / cm3 and the energy storage efficiency is 84%, while the energy storage density and energy storage efficiency of Example 2 are 3.08J / cm3 and 91%, respectively, and the energy storage density and energy storage efficiency of Example 3 are 2.07J / cm3 and 67%, respectively; and, with the increase of Gd content, the relaxation characteristics of the system at room temperature first increase and then weaken, and the breakdown field strength first increases and then decreases. When the Gd content reaches 0.25, the breakdown field strength reaches the maximum and the energy storage performance reaches the best. At the same time, with the increase of Gd content, its ferroelectricity is enhanced, the efficiency gradually decreases, the breakdown field strength decreases, and the energy storage characteristics of KRN-based ceramics decrease. The energy storage density and energy storage efficiency in Example 4 are only 0.14J / cm3 and 28%.

[0055] Table 1 shows the relevant performance parameters of Examples 1-4, wherein Example 1 has higher energy storage density and energy storage efficiency. By comparison, Example 1 has higher energy storage characteristics than Examples 2-4, and is more suitable for application in pulse power capacitor technology.

[0056] Table 1: Comparison of energy storage performance of KRN-based ceramics with different components

[0057] Components <![CDATA[Recyclable energy storage density Wrec (J / cm 3 )]]> Energy storage efficiency η(%) Example 1 X=0.75 4.46 84 Example 2 X=1 3.08 91 Example 3 X=0.5 2.07 67 Example 4 X=0.25 0.14 28

[0058] In summary, the embodiments of the present invention constitute a KRN-based room-temperature relaxor ceramic component. By regulating the ratio of different ions, the size of the A-site ion radius is regulated, so that the KRN-based ceramic exhibits excellent energy storage characteristics at room temperature, which greatly improves the energy storage performance of the KRN-based ceramic, and is suitable for the preparation and application of ceramic capacitors and dielectric capacitors in high-power pulse systems.

Claims

1. A lead-free relaxor ceramic material with tungsten bronze structure, characterized in that: The chemical composition of the ceramic material is: K2(LaxGd1-x)Nb5O15-2.5mol%MnCO3, wherein 0≤x≤1.

2. A tungsten bronze structure lead-free relaxor ceramic material as claimed in claim 1, characterized in that: The x value is 0.25≤x≤1.

3. A method for preparing a lead-free relaxor ceramic material with a tungsten bronze structure according to claim 1 or 2, characterized in that The following steps are involved: 1) According to the chemical composition ratio of the K2RENb5O15-based lead-free relaxor ceramic material, a K source, a Nb source, a La source, and a Gd source are mixed, and calcined to obtain an early solid solution powder; the powder is mixed with a Mn source to obtain a final solid solution powder; 2) mixing the final solid solution powder with a binder and granulating the mixture, and then aging, molding and extruding the mixture to obtain a ceramic green body; 3) The ceramic green body is sintered to obtain K2RENb5O15-based lead-free relaxor ceramic material.

4. The method for preparing a K2RENb5O15-based lead-free relaxor ceramic material as claimed in claim 3, characterized in that In step 1), the K source is K2CO3, the Gd source is Gd2O3, the La source is La2O3, the Nb source is Nb2O5, and the Mn source is MnCO3.

5. The method for preparing a lead-free relaxor ceramic material with a tungsten bronze structure as claimed in claim 3, characterized in that In step 1), the calcination temperature is 1200-1300° C. and the calcination time is 2-3 hours.

6. The method for preparing a lead-free relaxor ceramic material with a tungsten bronze structure as claimed in claim 3, characterized in that In step 2), the binder is at least one of polyvinyl alcohol, polyethylene glycol, polystyrene and methyl cellulose, the amount of binder added is 6-8wt% of the final solid solution powder, the aging temperature is room temperature, the time is 18-26 hours; the temperature of plastic removal is 650-850°C, and the time is 1-3 hours.

7. The method for preparing a lead-free relaxor ceramic material with a tungsten bronze structure as claimed in claim 3, characterized in that In step 3), the sintering temperature is 1200-1300° C. and the sintering time is 2-3 hours.

8. Use of a tungsten bronze structure lead-free relaxor ceramic material as claimed in any one of claims 1 to 7 in the preparation of ceramic components.

Citation Information

Patent Citations

  • Ferroelectric energy storage ceramic material with Gd-Ta co-doped tungsten bronze structure and preparation method of ferroelectric energy storage ceramic material

    CN114605151A

  • Dielectric ceramic composition and ceramic capacitor

    US20220028614A1